Effects of Different Patterns and Degrees of Openness in Superior-Subordinate Communication on Subordinate Job Satisfaction - Burke, Ronald J.; Wilcox, Douglas S. (Academy of Management Journal, 1969)
The proposition that open two-way communication is associated with a satisfying and effective superior-subordinate work relationship is examined. Different patterns and degrees of openness were related to five areas of subordinate work satisfaction. The results indicated that greater openness of communication by one or both members of the relationship was associated with increased satisfaction. In addition, openness of one member of the pair was significantly related to openness of the other members.